The Paulician Heresy: Contradiction of National and Universal - Nedolyan, Daniel (NAS RA)
Historical events always become the object of reinterpretation. The history of the Paulician heresy, which was widespread in medieval Armenia and Byzantium, is no exception. In this article, I will address the attempt to reinterpret the history of the Paulicians from a national-conservative position made by Karlen Mirumian. Analyzing his account of events and comparing it with the Soviet interpretation and a more detailed examination of the Paulician doctrine leads to interesting implications for understanding the specificity of the national discourse. The paper will compare the approaches to the interpretation of the role of the Paulicians in history given by Karlen Mirumyan and the Soviet author Hrant Bartikyan. Mirumyan's approach raises quite a few questions regarding methodology, especially his retrospective application of the framework of nationalist ideas to the feudal era. Besides, a more detailed study of the Paulician doctrine, conducted by Nina Garsoïan, shows us that the doctrine described by Mirumyan repeats the anti-Paulician propaganda of Byzantine authors, which has little in common with reality. All this allows us to move on to the peculiarities of Armenian nationalist ideology, which, when confronted with the Paulician phenomenon, reveals a surprising unity with the imperial discourse it is meant to oppose. That's why I turn to the ideas of the contemporary French philosopher Alain Badiou, who proposed the concept of three discourses - the discourse of homogenization, the discourse of exclusion, and the discourse of universalism. My assumption is that the Byzantine imperial discourse corresponds to the first, the nationalist discourse to the second, and the Paulician doctrine to the third, the universal discourse, against which the other two discourses merge.
Keywords: Political Studies; Political Philosophy